2018
DOI: 10.26596/wn.20189122-30
|View full text |Cite
|
Sign up to set email alerts
|

Can Taste Rating of Groundwater Samples for the Presence of Iron Be A Novel Approach to Groundwater Iron Assessment?

Abstract: Groundwater has been shown to contribute markedly to the daily iron intake of the rural Bangladeshi population and is currently characterized as an under-assessed possible source of dietary iron. Estimation of the levels of iron in groundwater in relation to dietary/nutritional assessments has been called for. However, the ability to do this may be limited due to unavailable equipment or technical, logistical and financial issues in remote areas of low-to middle-income countries. Groundwater with higher levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…(16) in rural northwestern Bangladesh and recently by Rahman et al. (22). We also validated this question in a subset of households ( n = 896) in 2017 ( Supplementa l File 1 ).…”
Section: Methodsmentioning
confidence: 87%
“…(16) in rural northwestern Bangladesh and recently by Rahman et al. (22). We also validated this question in a subset of households ( n = 896) in 2017 ( Supplementa l File 1 ).…”
Section: Methodsmentioning
confidence: 87%
“…Similarly, high Fe 3+ ingestion is not associated with any serious health risk. In natural waters, Fe 3+ concentrations may range from 0.5 to 50 mg/l [53,88]. Zinc concentration also differs significantly; in the Illo aquifer, mean Zn 2+ exceeds WHO and NSDWQ reference guidelines.…”
Section: Groundwater Chemistrymentioning
confidence: 99%
“…
The estimated prevalence of anaemia among children <5 years of age in low-and middle-income countries ranges from 41 to 44%, with half of these children suffering anaemia due to iron deficiency [1]. According to national surveys, the prevalence of anaemia in under-fives ranges from 33 to 51% in Bangladesh [2,3]. Previous studies have shown that groundwater iron provides a source of absorbable iron for humans and may enhance the iron and haemoglobin status of Bangladeshi populations [4][5][6][7].
…”
mentioning
confidence: 99%